The Role of Teachers in Shapingg Students’ Creativity in Inclusive Primary Shools - Mareza, Lia; Nugroho, Agung (Universitas Muhammadiyah Purwokerto, 2024)
This study aims to analyze the role of teachers in shaping the creativity of slow learner students in inclusive primary schools through the subject of Art, Culture, and Crafts (SBdP). The research employs a qualitative approach with a case study method at SD Negeri 5 Arcawinangun. The subjects include teachers, the principal, and seven slow learner students. Data were collected through observation, interviews, and documentation, and analyzed using triangulation methods. The results show that teachers play a crucial role in fostering students' creativity through various teaching strategies, such as providing repeated instructions, using visual media, and offering intensive guidance. Despite challenges such as low self-confidence and difficulties in time management, support from teachers, families, and the inclusive school environment helps students develop their creativity. This study emphasizes the importance of teachers' creativity in creating an inclusive and supportive learning environment.Â